Measuring adherence to unsupervised, conservative treatment for knee osteoarthritis: A systematic review. Issue 2 (June 2021) - Duong, Vicky; Daniel, Matthew S.; Ferreira, Manuela L.; Fritsch, Carolina G.; Hunter, David J.; Wang, Xia; Wei, Ni; Nicolson, Philippa JA.
Abstract: Objective: To describe the measurement of adherence to unsupervised, conservative treatments for knee osteoarthritis (OA), including the methods of adherence measurement, parameters for assessing adherence and any values used to quantify adherence. Methods: A systematic review with search terms related to knee OA, conservative treatments and adherence was conducted. The protocol was registered with the International Prospective Register of Systematic Reviews (registration number CRD42020158188). Seven electronic databases (MEDLINE, AMED, EMBASE, CINAHL, SportDiscus, PsychINFO, PEDro) were searched from inception to February 02, 2021. Studies that included unsupervised, conservative treatment(s) for knee OA measuring adherence were eligible. Studies were independently screened for inclusion by two researchers. Data was extracted by one researcher and verified by a second researcher. Extracted data included: study type, population, type of treatment, adherence measurement methods, time-points, recall, parameters and values used to quantify adherence. Results: Of 5033 references identified, 242 studies comprising of 261 treatments were included in the review. The majority of studies were randomised controlled trials investigating therapeutic exercise (n ​= ​107, 41.0%). The most common adherence measurement across all treatments was through self-reported diary (n ​= ​137, 52.5%) and the most common parameter was assessing the frequency of the treatment (n ​= ​79, 30.3%). Only a small number of studies provided values for quantifying satisfactory adherence (n ​= ​26, 9.3%). Conclusion: There is a wide variety in the reporting of adherence to conservative treatments for knee OA and standardised methods for measuring and reporting adherence are needed. Developing a tool to measure adherence to conservative treatments for knee OA is a priority.